Pendampingan Labelling Berbahasa Inggris pada Produk UMKM di Ranting Selabatu Cabang Cikole Kota Sukabumi - Susilawati, Lusi; Rachmawati, Ike; Hestiana, Siska; Komariah, Kokom; Juliansyah, Aris (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The purpose of this program is to make food product packaging better and more informative by adding English labelling, thus it could support the increase in sales of MSMEs products, as well as support the tourism development in  Sukabumi City. Methodology: The method was conducted through developing labelling, training on the text translation, and mentoring. Results: The result of this mentoring activity is the achievement of the level of comprehension and skills of MSMEs actors in terms of English packaging labelling which are proven by the printing of Mochi product packaging using the English translation version for ten types of products. Conclusions: The results of the assistance using labelling development, training, and mentoring methods show that the labelling mentoring participants have understood and can translate product packaging into English, so currently the product packaging has two languages printed as many as 1000 copies and ready to be marketed. Limitations: The limitation is only to the Mochi products due to the limited time and personnel. Contribution: It is expected that the result of this program will be beneficial to all the products produced by the MSMEs in Selabatu Twig Cikole Branch Sukabumi City.